Wyobrażenia i wiara w Boga dorosłych katolików w Polsce w drugiej połowie XX wieku i obu dekadach XXI wieku. Na podstawie wyników badań socjologicznych - Baniak, Józef (Humaniora. Czasopismo Internetowe, 2023)
In this article I present the attitude of adult Catholics in Poland in the second half of the 20th century and in both decades of the 21st century towards Theoentrical dogmas and the indicators of their faith in the religious meanning of these dogmas. The basis for the analysis of the attitude of adult Roman Catholics in Poland to these dogmas of the Christian faith are the results of sociological research carried out the turn of the 20th and 21st centuries. These studies showed that in the second half of the 20th century, a much greater percentage of adult Catholic in Poland accepted Theocentric dogmas and declared their faith in their religious mening than in both decades of the 21st century.